Use of expenditure analysis to enhance returns on investments in HIV services. Issue 5 (September 2017) - Honermann, Brian; O'Hagan, Richael
Abstract : Purpose of review: Globally, the response to the HIV epidemic is at a crisis point. International investments in the HIV response have been essentially flat for 8 years and domestic budgets in low and middle-income countries – still recovering from the global recession – have not been able to fill the resource gap to drive a full-fledged HIV response. Still, efficiencies and prioritization of evidence-based interventions enable a significant scale-up of treatment, but millions more people remain without treatment. This review looks at recent data and research to evaluate interventions that may help close gaps in service provision that undermine testing and treatment programs. Recent findings: The President's Emergency Plan for AIDS Relief recently began publicly releasing vast programmatic and expenditure data. These data reveal potential efficiency gaps in testing and treatment programs, particularly in the area of linkage and retention. Interventions such as HIV self-testing have been proposed to help, but whether they can deliver better results remains unclear. Same-day initiation on treatment improves initiation, retention, and viral suppression rates. Summary: Near real-time analysis of data and active response is critical in improving efficiencies in programs. More investment in implementation research is necessary to improve linkage to care and treatment to reach 90-90-90 goals.